2012
DOI: 10.4103/1463-1741.95133
|View full text |Cite
|
Sign up to set email alerts
|

Review of the effect of aircraft noise on sleep disturbance in adults

Abstract: Noise exposure generated by air traffic has been linked with sleep disturbances. The purpose of this systematic review is to clarify whether there is a causal link between aircraft noise exposure and sleep disturbances. Only complete, peer-reviewed articles published in scientific journals were examined. Papers published until December 2010 were considered. To be included, articles had to focus on subjects aged 18 or over and include an objective evaluation of noise levels. Studies were classified according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Many studies have demonstrated the adverse effects of exposure to aircraft noise on health, such as annoyance [5,6], sleep disturbance [7,8], cardiovascular diseases including hypertension [9,10,11,12,13], and alteration of cognitive performances among children [14,15]. The association between noise exposure and noise annoyance has been extensively investigated, and aircraft noise has been found to be the most annoying noise source among all transportation noise sources when standardized for noise exposure level [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the adverse effects of exposure to aircraft noise on health, such as annoyance [5,6], sleep disturbance [7,8], cardiovascular diseases including hypertension [9,10,11,12,13], and alteration of cognitive performances among children [14,15]. The association between noise exposure and noise annoyance has been extensively investigated, and aircraft noise has been found to be the most annoying noise source among all transportation noise sources when standardized for noise exposure level [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as underlined by the WHO recommendations on "Noise on health", airport noise may alter the ability of more vulnerable people to rest at night. Many studies have already been conducted on the effects of aircraft noise on sleep, and exposure to aircraft noise has been shown to disrupt sleep with an increased frequency of awakening, increased motility, decreased slow wave sleep, changes in sleep structure, use of sleep drugs or sedatives, a poor self-reported quality of sleep, an increased time for falling asleep, a decreased total sleep duration and an increased feeling of being tired while awakening in the morning (Jones & Rhodes, 2013;Michaud et al, 2007;Perron et al, 2012). However, the number of these studies investigating sleep duration is still limited and their results remain unclear (Perron et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already been conducted on the effects of aircraft noise on sleep; however, most of these studies are cross-sectional, with few prospective studies (Michaud, Fidell, Pearsons, Campbell, & Keith, 2007;Perron, Tetreault, King, Plante, & Smargiassi, 2012). In 5 both laboratory and field studies, exposure to aircraft noise has been shown to disrupt sleep (Basner, Griefahn, & Berg, 2010;Passchier-Vermeer, Vos, Steenbekkers, van der Ploeg, & Groothuis-Oudshoorn, 2002;Perron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations